2023
DOI: 10.1186/s13256-023-03848-7
|View full text |Cite
|
Sign up to set email alerts
|

Munchausen syndrome by proxy: a case report

Abstract: Background Inappropriately high levels of insulin secretion can cause the potentially fatal condition of persistent hyperinsulinemic hypoglycemia of infancy. Our paper focuses on another cause of severe hypoglycemia, which can be easily missed. Case presentation An 18-month-old Saudi female was referred to our hospital for further investigation and management of her recurrent hypoglycemic attacks as a case of persistent hyperinsulinemic hypoglycemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…A few other cases regarding MSBP in Saudi Arabia were reported, including a report by Al-Mugeiren and Ganelin about a 17-month-old Saudi male who presented with recurrent episodes of hematemesis, bleeding per rectum, and hematuria [ 10 ]. In addition, Alkhattabi et al reported a case of factitious hypoglycemia [ 11 ]. Overall, these case reports collectively underscore the presence of MSBP in Saudi Arabia and provide valuable clinical insights.…”
Section: Discussionmentioning
confidence: 99%
“…A few other cases regarding MSBP in Saudi Arabia were reported, including a report by Al-Mugeiren and Ganelin about a 17-month-old Saudi male who presented with recurrent episodes of hematemesis, bleeding per rectum, and hematuria [ 10 ]. In addition, Alkhattabi et al reported a case of factitious hypoglycemia [ 11 ]. Overall, these case reports collectively underscore the presence of MSBP in Saudi Arabia and provide valuable clinical insights.…”
Section: Discussionmentioning
confidence: 99%
“…2 FDIA is a psychiatric disease in which the caregiver induces symptoms of illness or harm in someone under their care, or attention from the treatment. 3,4 A person with FDIA may earn praise from others for their devotion to the dependent who's frequently hospitalized, and the dependent provides a way for the person with FDIA to develop relationships with physicians or other healthcare providers. In this way, the person gains attention from others by appearing to be a loving and compassionate caregiver of the dependent under their care.…”
mentioning
confidence: 99%
“…In this way, the person gains attention from others by appearing to be a loving and compassionate caregiver of the dependent under their care. 3,4 This disease is complex, misunderstood, and has severe consequences for the person who is abused, commonly individuals from vulnerable populations, such as children and older adults. 1 Consequences include negative impacts on the health and well-being of the targeted individuals, leading to physical and mental damage and sometimes death.…”
mentioning
confidence: 99%